Expression of the bitter receptor T2R38 in pancreatic cancer: localization in lipid droplets and activation by a bacteria-derived quorum-sensing molecule - Gaida, Matthias; Mayer, Christine; Dapunt, Ulrike A.; Stegmaier, Sabine; Schirmacher, Peter; Wabnitz, Guido H.; Hänsch, Gertrud Maria (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7206 Matthias M. Gaida, Christine Mayer, Ulrike Dapunt, Sabine Stegmaier, Peter Schirmacher, Guido H. Wabnitz, G. Maria Hänsch